The Galeng Tahun (10 Suro) Tradition as Oral Literature: Educational Values and Cultural Transmission in Beber Hamlet - Bambang Yoga Pranoto; Nazla Maharani Umaya; Setia Naka Andrian (Journal of Educational Sciences, 2026)
In the context of globalization and cultural change, local oral traditions play an important role as informal educational spaces for transmitting values and cultural knowledge. This study examines the Galeng Tahun (10 Suro) tradition as a form of oral literature that functions as a medium for educational values and cultural transmission in Beber Hamlet. Using a qualitative ethnographic approach, the research employs in-depth interviews, participatory observation, and document analysis to explore oral expressions embedded in ritual practices, including prayers, chants, advisory utterances, and narrative performances. The findings reveal that oral literature within the Galeng Tahun tradition serves significant educational functions by transmitting moral, social, and spiritual values across generations. These values are conveyed through symbolic language that fosters social harmony, respect for tradition, and awareness of the relationship between humans, nature, and the divine. Cultural transmission occurs through collective ritual participation, intergenerational storytelling, and community-based learning practices that enable younger generations to internalize local wisdom. Despite challenges posed by modernization, the Galeng Tahun tradition demonstrates continuity and adaptability as a form of informal cultural education. This study highlights oral literature as a valuable resource for value education and cultural sustainability within local communities.